2012
DOI: 10.4319/lo.2012.57.4.0989
|View full text |Cite
|
Sign up to set email alerts
|

Basin‐scale inputs of cobalt, iron, and manganese from the Benguela‐Angola front to the South Atlantic Ocean

Abstract: We present full-depth zonal sections of total dissolved cobalt, iron, manganese, and labile cobalt from the South Atlantic Ocean. A basin-scale plume from the African coast appeared to be a major source of dissolved metals to this region, with high cobalt concentrations in the oxygen minimum zone of the Angola Dome and extending 2500 km into the subtropical gyre. Metal concentrations were elevated along the coastal shelf, likely due to reductive dissolution and resuspension of particulate matter. Linear relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
199
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(231 citation statements)
references
References 70 publications
29
199
3
Order By: Relevance
“…Data on the distributions of the macronutrient elements N, P, Si [44,[62][63][64][65][66][67], the micronutrient elements Fe, Mn, Ni, Zn and Cd [64,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and the non-nutrient element Al [67,85,86] were downloaded from the IDP2014 collection [20] and imported into a Matlab™ environment for analysis. For each sampling location and/or seawater volume/water mass, a ranking of the relative deficiencies of multiple nutrient elements was calculated by dividing observed dissolved concentrations by an assumed 'typical' stoichiometric ratio within newly formed organic (biological) material (figure 1) [11,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the distributions of the macronutrient elements N, P, Si [44,[62][63][64][65][66][67], the micronutrient elements Fe, Mn, Ni, Zn and Cd [64,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and the non-nutrient element Al [67,85,86] were downloaded from the IDP2014 collection [20] and imported into a Matlab™ environment for analysis. For each sampling location and/or seawater volume/water mass, a ranking of the relative deficiencies of multiple nutrient elements was calculated by dividing observed dissolved concentrations by an assumed 'typical' stoichiometric ratio within newly formed organic (biological) material (figure 1) [11,18].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to providing confirmation of the ubiquity of sub-surface Fe deficiency within the ocean, results from the performed simple analysis can be further considered in the context of physical processes which return interior waters to the productive surface ( figure 5). Thus, in the absence of other local/regional sources/factors, such as interactions with sediments on the continental shelves [35,36], dust deposition [34] or specific sub-surface conditions including marked oxygen minima [84], any upwelled or upwardly mixed waters are likely to be deficient in Fe throughout the majority of the oceans. Development of Fe limitation in approximately 30% of the surface waters of the open ocean [11,19] should hence perhaps not be surprising.…”
Section: (B) Implications Of the Fe Deficiency Of The Sub-surface Oceanmentioning
confidence: 99%
“…Subsequent expansion of oxygen minimum zones could decrease the ocean inventory of fixed nitrogen species by increasing microbial denitrification and/or anaerobic ammonium oxidation. Expansion of oxygen minimum zones could also increase trace metal 66 and phosphorus inventories by increasing the release of these nutrients from sediments, as may have occurred over glacial-interglacial cycles (see Supplementary Information). Such changes at depth could influence surface waters on timescales of decades or longer (Fig.…”
Section: Nature Geoscience Doi: 101038/ngeo1765mentioning
confidence: 99%
“…These waters are deficient in those trace metals that have short oceanic residence times due to scavenging losses (Fig. 1a,d) 6,66 , contributing to the tendency for iron limitation in the Southern Ocean (Fig. 3).…”
Section: Potential For Changementioning
confidence: 99%
“…Actually, distinguishing the riverine solid load from the deposited sediments is not straightforward in coastal environments, owing to the fact that they essentially refer to the freshness of the material. However, recent works identified that submarine weathering of deposited material can act as a source of trace elements and isotopes to the ocean, allowing the present distinction of this later pathway [13][14][15][16][17][18][19]. -Submarine groundwater discharges (SGD).…”
Section: Introductionmentioning
confidence: 99%